Efforts to Improve RA Learners' Understanding of the Solar System Through Interactive Learning Media at Sholawat Islamic Boarding School - Septianto, Tri; Kusbandono, Hendrik; Sumafta, Ikhwan Baidlowi; Muniruddin, Agus; Wardani, Dirajati Kusuma; Annisya, Annisya (Unram Journal of Community Service, 2024)
This community service aims to improve the understanding of students at RA Pondok Sholawat, Caruban, Madiun, East Java, about the Solar System through interactive learning media. Based on the initial observations, it was found that traditional learning methods cannot attract interest and improve students' understanding optimally. To overcome this problem, an intervention was carried out in the form of a grant for a set of touchscreen laptops and training teachers on using interactive learning media. The results showed an increase in the enthusiasm and involvement of students in the learning process and an increase in teacher competence in utilizing technology as a learning tool. This program created a more pleasant and effective learning atmosphere and positively impacted the quality of learning at RA Pondok Sholawat. Interactive learning media is expected to be an innovative model that can be applied in other educational institutions to improve students' understanding of scientific concepts from an early age.